LPS from P. gingivalis Negatively Alters Gingival Cell Mitochondrial Bioenergetics - Kiran Napa; Andrea C. Baeder; Jeffrey E. Witt; Sarah T. Rayburn; Madison G. Miller; Blake W. Dallon; Jonathan L. Gibbs; Shalene H. Wilcox; Duane R. Winden; Jared H. Smith; Paul R. Reynolds; Benjamin T. Bikman (International Journal of Dentistry)
Objective. Oral inflammatory pathologies are linked to increased oxidative stress, thereby partly explaining their relevance in the etiology of systemic disorders. The purpose of this work was to determine the degree to which LPS from Porphyromonas gingivalis, the primary pathogen related to oral inflammation, altered gingival mitochondrial function and reactive oxygen species generation. Methods. Human gingival fibroblast (HGF-1) cells were treated with lipopolysaccharide of P. gingivalis. Mitochondrial function was determined via high-resolution respirometry. Results. LPS-treated HGF-1 cells had significantly higher mitochondrial complex IV and higher rates of mitochondrial respiration. However, this failed to translate into greater ATP production, as ATP production was paradoxically diminished with LPS treatment. Nevertheless, production of the reactive H2O2 was elevated with LPS treatment. Conclusions. LPS elicits an increase in gingival cell mitochondria content, with a subsequent increase in reactive oxygen species production (i.e., H2O2), despite a paradoxical reduction in ATP generation. These findings provide an insight into the nature of oxidative stress in oral inflammatory pathologies.